The Anatolian Journal of Cardiology 2021
DOI: 10.5152/anatoljcardiol.2021.25905
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular characteristics of noncompaction phenotype patients with good ejection fraction measured with cardiac magnetic resonance

Abstract: Objective: We describe left ventricular (LV) volumes, myocardial and trabeculated muscle mass and strains with Cardiac magnetic resonance of a large cohort (n=81) who fulfilled the morphologic criteria of left ventricular noncompaction (LVNC) and had good ejection fraction (EF >55%) and compare them with healthy controls (n=81). Male and female patients were compared to matched controls and to each other. We also investigated the LV trabeculated muscle mass cutoff in male and female patients with LVNC. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“… 1 It was concluded that LV functional and strain characteristics of the LVHT cohort differ 2 significantly from healthy controls. 1 Since the LV muscle mass was larger in men as compared to females, gender-specific diagnostic criteria are warranted. 1 We have the following comments and concerns.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“… 1 It was concluded that LV functional and strain characteristics of the LVHT cohort differ 2 significantly from healthy controls. 1 Since the LV muscle mass was larger in men as compared to females, gender-specific diagnostic criteria are warranted. 1 We have the following comments and concerns.…”
mentioning
confidence: 98%
“… 1 Left ventricular hypertrabeculation patients nonetheless had increased LV volume, LV mass, reduced LV ejection fraction, and reduced global circumferential strain. 1 It was concluded that LV functional and strain characteristics of the LVHT cohort differ 2 significantly from healthy controls. 1 Since the LV muscle mass was larger in men as compared to females, gender-specific diagnostic criteria are warranted.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to thank you for the opportunity to reply to the comments and concerns raised in the author’s letter to the Editor and to give details about the patient population included in our study. 1 We would also like to thank the author for his interest in our paper and for taking the time to express their concerns.…”
mentioning
confidence: 99%